Anthropometric indices and measures to assess change in the nutritional status of a population: a systematic literature review. Issue 1 (December 2016) - Frison, Severine; Kerac, Marko; Checchi, Francesco; Prudhon, Claudine
Abstract Background Undernutrition is a major public health issue highlighted by the 2015 Sustainable Development Goals, with target 2.2 aiming to 'end hunger' by 2030. On-going surveillance is essential detecting nutritional stress in a population and is key to planning consequent interventions. Whilst methodologies of nutritional surveillance systems vary across different settings, organisations and even within the same country, the direct evidence-base underpinning these practices is limited. This paper aims therefore to: 1) compare the performance of different anthropometric indices/measurements for detecting change in the nutritional situation at population level; 2) discuss their properties and appropriateness for use in a surveillance system. Methods This systematic literature review considered peer-reviewed and grey literature. Evidence was compiled from standard electronic databases, websites and snowballing. The search was performed in November 2015 by a single reviewer using the following terms to capture two concepts: 1) Undernutrition and 2) Nutrition surveillance. The search was limited to children under five and the period considered started in 1980. Languages included English and French. Articles had to assess whether the changes or trend observed at population level were statistically significant. All study designs were included. Results A total of 4563 articles were retrieved from the electronic database search. Most articles (3137, 89%) were not directly relevant based on title and abstract; 39 articles were reviewed in full. A total of 17 articles met the inclusion criteria and an additional 4 papers were added after snowballing. A number of measures and indices such as weight, weight-for-height/length, triceps skinfold and middle-upper arm circumference performed well in the detection of short term changes in the nutritional situation of a population. Height/Length-for-age responded the most to long term change. Applying a standard set of criteria (simplicity, acceptability, cost, independence of age, reliability and accuracy) to determine which is the most appropriate measure or index identified middle-upper arm circumference as the one with the greatest net benefits. Conclusions Limited available evidence suggests that mid-upper arm circumference is the best measure to detect short term changes in the nutritional state of a population: this should receive higher priority in surveillance systems.